Loss of cysteine 584 impairs the storage and release, but not the synthesis of von Willebrand factor - Daidone, Viviana; Barbon, Giovanni; Pontara, Elena; Cattini, Grazia M.; Gallinaro, Lisa; Zampese, Enrico; Pizzo, Paola; Casonato, Alessandra (Thrombosis and Haemostasis, 2014)
Cysteines play a key part in von Willebrand factor (VWF) dimerisation and polymerisation, and their loss may severely affect VWF structure and function. We report on three patients with type 3 von Willebrand disease carrying the new c.1751G>T missense mutation that induces the substitution of cysteine 584 by phenylalanine (C584F), and the deletion of seven nucleotides in exon 7 (c.729_735del), producing a premature stop codon at position 454 (E244Lfs*211). VWF was almost undetectable in the patients’ plasma and platelets, while a single, poorly represented, oligomer emerged on plasma VWF multimer analysis. No post-DDAVP increase in VWF and factor VIII was observed. Expressing human recombinant C584F-VWF in HEK293T cells showed that C584F-VWF was synthesised and multimerised but not secreted – apart from the first oligomer, which was slightly represented in the conditioned medium, with a pattern similar to the patients’ plasma VWF. The in vitro expression of the E244Lfs*211–VWF revealed a defective synthesis of the mutated VWF, with a behavior typical of loss of function mutations. Cellular trafficking, investigated in HEK293 cells, indicated a normal C584F-VWF content in the endoplasmic reticulum and Golgi apparatus, confirming the synthesis and multimerisation of C584F-VWF. No pseudo-Weibel Palade bodies were demonstrable, however, suggesting that C584F mutation impairs the storage of C584F-VWF. These findings point to cysteine 584 having a role in the release of VWF and its targeting to pseudo-Weibel Palade bodies in vitro, as well as in its storage and release by endothelial cells in vivo.
Keywords: von Willebrand factor; von Willebrand disease; VWF propeptide; VWF gene mutations; VWF multimerisation